E-Government Development Strategy in Tambak Kalisogo and Panggreh Villages Towards Optimizing Document Administration: Strategi Pengembangan E-Government di Desa Tambak Kalisogo dan Panggreh Menuju Optimalisasi Administrasi Dokumen - Choiriyah, Ilmi Usrotin; Rodiyah, Isnaini; Bahlamar, Ahmad Riyadh Umar; Rustianingsih, Eni (Universitas Muhammadiyah Sidoarjo, 2025)
This study analyzes the E-Government development strategy in Tambak Kalisogo and Panggreh Villages, Sidoarjo Regency, with a focus on optimizing document administration. The background of this study is the importance of E-Government in improving the efficiency and transparency of public services at the village level. The purpose of this study is to identify elements of the E-Government development strategy and compare its implementation in both villages. The research method used is descriptive qualitative with data collection through literature study methods. The subjects of the study were village officials in Tambak Kalisogo and Panggreh, as well as documents related to village administration. Data analysis was carried out based on the ITPOSMO framework (Information, Technology, Process, Objectives and Values, Staff and Skills, Management, and Other Resources). The results of the study show that Panggreh Village is superior in developing E-Government compared to Tambak Kalisogo Village, especially in terms of implementing the E-Buddy application, technology infrastructure, and HR skills. The conclusion of this study is that optimizing document administration through E-Government requires investment in infrastructure, improving HR skills, and strong management support. This study contributes to the development of public administration science by identifying key factors for the success of E-Government implementation at the village level. The recommendation of this study is that Tambak Kalisogo Village can learn from the implementation strategy in Panggreh Village to improve the efficiency and transparency of document administration. This study identifies key factors for the success of E-Government at the village level.